Enhancing recombinant protein production through Cre-loxP mediated chromosomal rearrangement evolution in Kluyveromyces marxianus - Haiyan Ren; Qiyuan Zou; Kunfeng Song; Yao Yu; Jungang Zhou; Wenjuan Mo; Hong Lu (Communications Biology)
Abstract Chromosomal rearrangements can drive adaptive evolution; however, whether the rearrangements in non-coding and non-promoter regions can lead to new phenotypes under selective pressures remains unclear. Additionally, highly producing recombinant proteins is a key industrial task but poses stress on host cells. Therefore, it is desirable to investigate the role of chromosomal rearrangement in non-coding and non-promoter regions during high-yield recombinant protein phenotype formation. In this study, we utilize the Kluyveromyces marxianus strain as the host for recombinant protein production, with the recombinant fusion protein comprising leghemoglobin (LBA) and enhanced green fluorescent protein serving as a reporter. Iterative evolution is conducted to select high-yield strains using Cre-loxP mediated chromosomal rearrangement technology and high-throughput fluorescence intensity screening. The evolved strains exhibit ~seven-fold increase in fluorescence intensity and a 1.7-fold improvement in LBA yield, identified with chromosome VIII inversion and chromosomes III and V translocation. Introducing these rearrangements into wild-type strains significantly increase recombinant protein yield to about 1.5-fold. Cascade networks are reconstructed based on RNA-seq analysis to elucidate rearrangements’ impact on global metabolic processes. Our study confirms that chromosomal rearrangements in non-coding regions can establish adaptive phenotypes and provides new ways of engineering host cells to improve recombinant protein productivity.